Impact of recycled concrete aggregate on mechanical and durability properties of concrete paver blocks. (2021) - Attri, Gyanendra Kumar; Gupta, R.C.; Shrivastava, Sandeep
Abstract: Indian Construction industry is facing shortage of natural aggregates due to limited availability & ban on extraction of raw material. In this study, natural coarse aggregate (NCA) and river sand (RS) in conventional paver block were replaced by recycled concrete aggregates (RCA). Mechanical and durability properties i.e., density, compressive strength, water absorption, abrasion resistance and ultrasonic pulse velocity of the paver blocks were investigated. It was found that coarse RCA can replace up to 45% NCA and fine RCA may replace up to 40% RS without having significant impact on properties of the paver blocks.